Short‐Term Effect of Estrogen on Human Bone Marrow Fat. (14th July 2015) - Limonard, Eelkje J; Veldhuis‐Vlug, Annegreet G; van Dussen, Laura; Runge, Jurgen H; Tanck, Michael W; Endert, Erik; Heijboer, Annemieke C; Fliers, Eric; Hollak, Carla E; Akkerman, Erik M; Bisschop, Peter H
Abstract Bone marrow fat, an unique component of the bone marrow cavity increases with aging and menopause and is inversely related to bone mass. Sex steroids may be involved in the regulation of bone marrow fat, because men have higher bone marrow fat than women and clinical observations have suggested that the variation in bone marrow fat fraction is greater in premenopausal compared to postmenopausal women and men. We hypothesized that the menstrual cycle and/or estrogen affects the bone marrow fat fraction. First, we measured vertebral bone marrow fat fraction with Dixon Quantitative Chemical Shift MRI (QCSI) twice a week during 1 month in 10 regularly ovulating women. The vertebral bone marrow fat fraction increased 0.02 (95% CI, 0.00 to 0.03) during the follicular phase (p = 0.033), and showed a nonsignificant decrease of 0.02 (95% CI, –0.01 to 0.04) during the luteal phase (p = 0.091). To determine the effect of estrogen on bone marrow fat, we measured vertebral bone marrow fat fraction every week for 6 consecutive weeks in 6 postmenopausal women before, during, and after 2 weeks of oral 17‐β estradiol treatment (2 mg/day). Bone marrow fat fraction decreased by 0.05 (95% CI, 0.01 to 0.09) from 0.48 (95% CI, 0.42 to 0.53) to 0.43 (95% CI, 0.34 to 0.51) during 17‐β estradiol administration (p < 0.001) and increased again after cessation. During 17‐β estradiol administration the bone formation marker procollagen type I N propeptide (P1NP) increased (p = 0.034) and the bone resorption marker C‐terminal crosslinking telopeptides of collagen type I (CTx) decreased (p < 0.001). In conclusion, we described the variation in vertebral bone marrow fat fraction among ovulating premenopausal women. And among postmenopausal women, we demonstrated that 17‐β estradiol rapidly reduces the marrow fat fraction, suggesting that 17‐β estradiol regulates bone marrow fat independent of bone mass. © 2015 American Society for Bone and Mineral Research.